A comparison of the acid mine drainage (AMD) neutralization potential of low grade nickel laterite and other alkaline-generating materials - Turingan, Casey Oliver A. (Animo Repository, 2020)
Acid mine drainage (AMD) is a serious environmental problem caused by the weathering of sulfur-rich minerals found in mine sites, typically pyrite. Passive treatment methods have been extensively studied exploring various materials and treatment systems. Limestone is typically used as neutralizing media through open channels or anoxic limestone drains. However, the armouring that occurs when heavy metals precipitate on the surface restricts the lifespan of limestone treatment systems to 15-20 years. Goethite has been characterized to be a good adsorbent of heavy metals found in wastewater. It is abundant in a layer of nickel laterite deposit which are considered mine wastes due to the low amount of nickel present. This study investigates the performance of locally available nickel laterite ore rock, limestone, fly ash, and cement waste as media for AMD neutralization. The treatment efficiency are evaluated based on the physiochemical properties of the AMD, namely: pH, redox potential (ORP), conductivity, total dissolved solids (TDS), and dissolved oxygen (DO). © 2020 IOP Publishing Ltd.